Clinical important of E-Cadherin, CA15-3 and CEA in Diagnostic and Flow Up for Breast Cancer Patients - Alaa Haleem Imran; Sahib Ali Al-atrachji; Karar Kadhim Al-mosawi (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: The normal prevailing cancer in the women is Breast cancer, other than nonmelanoma skincancer. E-cadherin performs an essential role in epithelial cell adhesion and the decline of its role is the maindonor to cancer rise because the majority of solid tumors are carcinomas that occur from epithelial tissue. Asegment of the mucin-1 (MUC-1) is the cancer antigen 15-3 (CA15-3) order of glycoproteins, is classifiedas a serviceable tumor marker inspired by revised glycosylation of itself. The carcinoembryonic antigen(CEA) levels is raise in the blood, as a sort of cell adhesion molecule are associated with tumor metastasis.Methods A cross-sectional study held implemented on100 specimens, 50 patient with breast cancer ere andsubsequent chemotherapy therapy with 50 healthy individuals (healthy patients).Results The result reveals significant disparities patient group the same patient as a novel cause, followinginitial chemotherapy procedure and matched with the control group in some tumors markers such as (CA15-3, CEA) exact (E-cadherin) shows non-significant.Conclusions Our cross-sectional study designates that the E-Cadherin was non-significant for breast cancerpatients including Tumors markers (CA15-3, CEA) bestows significance with breast cancer patients.